IMPLEMENTASI EDUKASI DAN MOTIVASI TERPADU SEKOLAH–GEREJA DALAM MENINGKATKAN MINAT LANJUTKAN PENDIDIKAN TINGGI PADA PEMUDA DESA BAHU PALAWA - Matthew Timothy Palit; Rossa Hermelia; Sella Vinisya; Eritya; Joan Amazia; Puput; Yemima Nathalia; Olivtia Kesia Pebriany; Alfinia Tecuari; Cicha Widia; Sarmauli; Andi Pratama (Adiba Aisha Amira, 2025)
This study examines the implementation of the Integrated School–Church Education and Motivation program aimed at increasing the interest of youth in pursuing higher education in Bahu Palawa Village. The small village, with approximately 515 residents, faces declining tertiary education aspirations, early marriage, negative digital content influence, and low youth participation in religious activities. Using a qualitative descriptive approach, data were collected through participatory observation, in depth interviews with stakeholders (village head, teachers, church leaders, and youth), and documentation of the KKN program. Findings indicate that the school–church synergy via career roadmap workshops, public speaking training, digital literacy outreach, and spiritual fellowships effectively boosts learning motivation, reduces tendencies for early marriage, and improves youths’ digital habits. The program also revitalized youth engagement in religious service. In conclusion, this integrated school–church model is an effective contextual intervention to foster long-term educational orientation and character formation among rural youth in similar settings.